Effects of experimental hyperlipoproteinaemia on the retina and optic nerve in rhesus monkeys. - Yanko, L (1983)
Hyperlipoproteinaemia resulting from thyroid suppression and long-term ingestion of a high cholesterol diet caused prolonged lipaemia retinalis in 6 rhesus monkeys. No atherosclerotic deposits or other ophthalmoscopically visible changes of the retinal vasculature were detectable. In 2 animals histopathological examination revealed segmental atrophy and gliosis of the optic nerves bearing a resemblance to chronic ischaemic optic neuropathy. One monkey developed ophthalmoscopically visible temporal pallor of the optic discs. Emboli of fat laden cells in blood vessels of the brain in one of these 2 monkeys, and in a penicillated splenic artery in the other animal, were associated with signs of systemic embolic occlusion, suggesting a similar course in the development of optic nerve damage.